2017
DOI: 10.1093/jrr/rrx050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of texture analysis of 18F-FDG PET/CT in patients with Stage I lung cancer treated with stereotactic body radiotherapy

Abstract: We evaluated the reproducibility and predictive value of texture parameters and existing parameters of 18F-FDG PET/CT images in Stage I non-small-cell lung cancer (NSCLC) patients treated with stereotactic body radiotherapy (SBRT). Twenty-six patients with Stage I NSCLC (T1-2N0M0) were retrospectively analyzed. All of the patients underwent an 18F-FDG PET/CT scan before treatment and were treated with SBRT. Each tumor was delineated using PET Edge (MIM Software Inc., Cleveland, OH), and texture parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
2
22
0
2
Order By: Relevance
“…High-order features, in particular, coarseness, from 18 F-FDG PET have also shown predictive and prognostic capability in NSCLC patients who underwent chemoradiation therapy (57) . A retrospective study of 26 patients with stage 1 NSCLC tested standard metrics and texture parameters in pretherapy (SBRT) 18 F-FDG PET/CT scans for the prediction of local control, progression-free, and overall survival (59) . Although most features showed good interobserver reproducibility, only the texture feature of high-intensity large area emphasis predicted for local control ( P = .03) and SUVmax for progression-free survival ( P = .03), with no PET parameters found for overall survival on univariate analysis.…”
Section: Radiomics and Texture Analysis In Radiation Therapymentioning
confidence: 99%
“…High-order features, in particular, coarseness, from 18 F-FDG PET have also shown predictive and prognostic capability in NSCLC patients who underwent chemoradiation therapy (57) . A retrospective study of 26 patients with stage 1 NSCLC tested standard metrics and texture parameters in pretherapy (SBRT) 18 F-FDG PET/CT scans for the prediction of local control, progression-free, and overall survival (59) . Although most features showed good interobserver reproducibility, only the texture feature of high-intensity large area emphasis predicted for local control ( P = .03) and SUVmax for progression-free survival ( P = .03), with no PET parameters found for overall survival on univariate analysis.…”
Section: Radiomics and Texture Analysis In Radiation Therapymentioning
confidence: 99%
“…While recent work has evaluated the potential for radiomics features to augment traditional metrics of response (1012), the majority of studies to date have focused on only the metabolic tumor volume (MTV) on PET and, to the best of our knowledge, no study has investigated the peritumoral region. Tumor invasion from the main mass can be defined by infiltration of stroma, blood vessels, or visceral pleura (13).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in our study the average predictive performance for GLM all in all clinical endpoints ranged from 0.50 to 0.66. For comparison, other studies predicting outcome with both PET radiomics and clinical variables in NSCLC found predictive performances of 0.63 for predicting OS [41], 0.72 for local recurrence [71], and 0.71 for distant metastases [72]. Even with those results, neglecting any limitations of those studies, there is still no strong evidence that PET texture features exhibit complementary information.…”
Section: Discussionmentioning
confidence: 89%